Plasma Micronutrients (magnesium, zinc, selenium) Status and Lipid Profile in Type II Diabetes Mellitus Patients in Sagamu, Southwestern Nigeria - Olooto WE; Ifabumuyi TA; Odusan O; Olawale OO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Diabetes mellitus (DM) is a group of metabolic disorders characterised by hyperglycemia with secondary derangements in micronutrient status. Various studies had given conflicting reports of increased or decreased levels of micronutrients in Type II DM. Objective: To measure the plasma micronutrient levels and lipid profile in adults with Type II DM. Method: Plasma magnesium, zinc and selenium levels were measured among 100 subjects comprising 50 people with DM (age range 36-70 years) and 50 control subjects without DM (age range 29-70 years). The anthropometric parameters were measured; fasting blood glucose, plasma cholesterol, triglycerides, and high-density lipoprotein cholesterol, micronutrients (magnesium, zinc and selenium) levels were also measured using standard methods. Result: There were statistically significant (p < 0.05) higher plasma glucose, blood pressure (systolic and diastolic), LDLC, and lower levels of plasma magnesium, zinc, selenium, HDLC levels among the patients with DM (cases) compared with the normal control subjects. No significant difference was observed in the plasma total cholesterol and triglyceride between the two groups. A significant negative correlation was found between the plasma levels of the trace metals (magnesium, zinc and selenium) and triglycerides (r = - 0.36, r = - 0.43, r = - 0.51 respectively). Conclusion: Plasma levels of magnesium, zinc and selenium are reduced in Type II DM with associated hyperglycaemia-driven dyslipidaemia.